2016
DOI: 10.21873/anticanres.11040
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of BRAF Mutations in Colorectal Cancer Liver Metastases

Abstract: BRAF-mutant lesions are consistently associated with poor prognosis. Consequently, the indications of CRLM resection in this patient group should be reconsidered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 37 publications
1
9
0
3
Order By: Relevance
“…CRC that carry BRAF mutations have been associated with poor prognosis. BRAF mutations are more frequent in right colon tumors, poorly differentiated, with a mucinous histology and infiltrating lymphocytes that are usually MSI-High [ 30 ]. Approximately 8% of CRC carry the distinct BRAF V600E mutation.…”
Section: Braf Mutationsmentioning
confidence: 99%
“…CRC that carry BRAF mutations have been associated with poor prognosis. BRAF mutations are more frequent in right colon tumors, poorly differentiated, with a mucinous histology and infiltrating lymphocytes that are usually MSI-High [ 30 ]. Approximately 8% of CRC carry the distinct BRAF V600E mutation.…”
Section: Braf Mutationsmentioning
confidence: 99%
“…Several research groups have provided evidence that two proto-oncogenes, KRAS and BRAF , are associated with resistance to chemotherapy and poor prognosis [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ], as confirmed by the survival analysis of the BRAF mutated CRCLM included in the TCGA cohort ( Figure 4 B).…”
Section: Resultsmentioning
confidence: 83%
“…Differences in outcome are undoubtedly related not only to LT, but also strict patient selection. To this point, patients with poor prognostic risk factors for recurrence and survival after CLM resection were excluded from the SECA study …”
Section: Discussionmentioning
confidence: 99%
“…Differences in outcome are undoubtedly related not only to LT, but also strict patient selection. To this point, patients with poor prognostic risk factors for recurrence and survival after CLM resection were excluded from the SECA study 59,60. More recent data from the NORDIC VII study have suggested results in favor of LT over standard chemotherapy for unresectable CLM in light of the only 9% 5-year OS among patients receiving firstline combination chemotherapy only 61.…”
mentioning
confidence: 99%